2009
DOI: 10.1007/s00419-009-0390-2
|View full text |Cite
|
Sign up to set email alerts
|

Contact stresses: a short survey of models and methods of computations

Abstract: Contact stresses are identified as normal and tangential forces between contacting solids. The normal stresses are modeled using unilateral and complementary conditions, elastic response and normal compliance. Friction laws describe the tangential traction. Friction of materials depends on pressure, sliding velocity, surface temperature, time of contact, surface roughness and presence of wear debris. Phenomenological, micromechanical and atomic-scale models as well as non-classical models of anisotropic and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 127 publications
(176 reference statements)
1
10
0
Order By: Relevance
“…Some works in the literature have studied and developed different friction models. Curnier [1] presents a general theory of friction, Michalowski and Mróz [2] and Mróz and Stupkiewicz [3] consider an orthotropic model with a non-associated sliding rule, and Zmitrowicz [4][5][6][7] takes into account more sophisticated friction models.…”
Section: Introductionmentioning
confidence: 99%
“…Some works in the literature have studied and developed different friction models. Curnier [1] presents a general theory of friction, Michalowski and Mróz [2] and Mróz and Stupkiewicz [3] consider an orthotropic model with a non-associated sliding rule, and Zmitrowicz [4][5][6][7] takes into account more sophisticated friction models.…”
Section: Introductionmentioning
confidence: 99%
“…Some models assume frictionless contact and others add continuum models of adhesion to the elements. A survey of numerical modeling techniques and methods used to determine contact stresses is found in [26]. Megalingam et al reviews all existing models and provides a comprehensive elastic-plastic single-asperity contact model [23].…”
Section: Contact Mechanicsmentioning
confidence: 99%
“…It can be shown that integrals in the third equation of system (25) is equal to zero for elliptical and circular contact areas. So, finally we have:…”
Section: General Considerationsmentioning
confidence: 99%